The impact of organizational climate on total quality management in higher education organizations: an analytical study on a sample of University of Basrah faculty members - Jahloul, Iman (The Gulf Economist, 2024)
The research aims to determine the organizational impact of climate on achieving total quality management from the point of view of teachers at the University of Basra. The analytical descriptive model was relied upon for the comprehensive questionnaire for the data sets from the study population, which amounted to 2,500 intentional innovators with a simple Belgian sample of 333 innovators from various colleges at the university, using the statistical program (SPSS.v24 ) to ensure the validity. 345 questionnaires were distributed. The retrieved questionnaires were 338 questionnaires, but the valid questionnaires were For statistical analysis, there were 335 questionnaires, with a percentage of members (97%). The results of the research were based on the validity of the hypotheses, and may include searching for a number of important signals. The University of Basrah asserted the importance of activating organizational work in order to achieve comprehensive quality management in our educational methods, with the aim of achieving this. It holds university graduates from the workforce which is reflected in joining organizations in the entire country.